Minimasi Waktu Tunggu pada Proses Disassembly Engine dengan Pendekatan Lean Manufacturing di PT OPQ - Seviolla, Geyska; Muqimuddin, Muqimuddin; Purba, Arini Anestesia; Ismail, Andi Idhil (Fakultas Teknik Universitas Tulang Bawang, 2024)
Balikpapan is one of the regions in Indonesia that has a remanufacturing business center. PT OPQ is one of the remanufacturing companies with an engine disassembly process that experiences over lead time for 3 years which reaches 2,003 minutes which exceeds the standard for 1,845 minutes due to non-value added activities such as idling, waiting for components, waiting for component files, arranging components, and chatting in the engine disassembly process. This research aims to minimize the time of non-value added activities in the engine disassembly process. This research method uses lean manufacturing with identification stages with process activity mapping, value stream mapping, pareto diagram, and fault tree analysis, as well as providing proposed recommendations. The results showed a decrease in engine disassembly cycle time from 1,874 minutes to 1,615 minutes. Proposed improvements that can be recommended in the form of engine scheduling produce production capacity per month for 1 operator can complete 6 engines, arrange components according to the type of engine components that have been divided for each area, and the application of shortest job first which results in a decrease in lead time between processes which originally reached 1,985 to 1,051 minutes or decreased by 1,900 minutes for the total from before and after improvement. Keywords: Lead Time, Lean Manufacturing, Waste Waiting